Leveraging Cloud Native Development for Ecosystem Strategy - Raghu Venkatesh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the intersection of cloud-native development and business ecosystem strategies, highlighting how cloud-native technologies create scalable, flexible, and interoperable platforms that foster collaboration and innovation. It examines the composition and dynamics of business ecosystems, the key advantages of cloud-native development for ecosystem strategies, and practical approaches for implementing cloud-native ecosystem platforms. The paper provides insights into the transformative potential of these technologies in shaping modern business ecosystems, supported by market data, case studies, and industry trends.
Keywords: Cloud-Native Development; Business Ecosystems; Microservices Architecture; API-Driven Integration; Containerization